BLOOD SUPPLY TO THE HUMAN BODY, VASCULAR ANATOMY AND BLOOD COMPONENTS - Alimov N (Western European Studies, 2023)
Blood, fluid that transports oxygen and nutrients to the cells and carries away carbon dioxide and other waste products. Technically, blood is a transport liquid pumped by the heart (or an equivalent structure) to all parts of the body, after which it is returned to the heart to repeat the process. Blood is both a tissue and a fluid. It is a tissue because it is a collection of similar specialized cells that serve particular functions. These cells are suspended in a liquid matrix (plasma), which makes the blood a fluid. If blood flow ceases, death will occur within minutes because of the effects of an unfavourable environment on highly susceptible cells.
Keywords: blood; causes; fluid